The status of development of nanoparticle-based swine influenza vaccines: A review - Poudel, Uddab; Pantha, Saurav; Kaphle, Krishna (Journal of Biomedical Sciences, 2019)
Background Swine are the most important meat animal, famous for white meat, which are prepared as ham, bacon, gammon, sausages and pork. Swine are valuable animals and they are physiologically, immunologically and anatomically similar to humans and their organ can be transplanted to the humans. Due to modernization, the cultural food restriction has lost in the people of urban communities and among the younger generations in Nepal. Gradually changing feeding habit of Nepalese has proven pork to be a useful addition to the food menu. Not only 8.7 lakhs swine in Nepal but the global pig population which occupy 769.05 million are suffering every day from new challenges and threats from very harmful pathogens and diseases like swine dysentery, coccidiosis, swine influenza, etc. Swine influenza is highly contagious rapidly spreading zoonotic viral disease of pigs characterized by febrile respiratory disease often complicated with secondary bacterial infections. Vaccines are only tool for prophylactic measures. There is big challenge for vaccine researchers, manufacturers and scientists for development of effective vaccine regarding swine influenza. Currently available flu vaccines are capable of homologous protection of virus but fail to induce cross protection against frequently evolving heterologous viruses. In this review, we discuss the status of novel nanoparticle-based approach of swine influenza virus vaccine development contributed significantly by Nepalese scientist and the future directions to control this economically important swine disease.